2007
DOI: 10.1016/j.mce.2006.10.012
|View full text |Cite
|
Sign up to set email alerts
|

A physiological role for glucuronidated thyroid hormones: Preferential uptake by H9c2(2-1) myotubes

Abstract: Conjugation reactions are important pathways in the peripheral metabolism of thyroid hormones. Rat cardiac fibroblasts produce and secrete glucuronidated thyroxine (T4G) and 3,3 ,5-triiodothyronine (T3G). We here show that, compared to fibroblasts from other anatomical locations, the capacity of cardiofibroblasts to secrete T4G and T3G is highest. H9c2(2-1) myotubes, a model system for cardiomyocytes, take up T4G and T3G at a rate that is 10-15 times higher than that for the unconjugated thyroid hormones. T3 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 56 publications
(61 reference statements)
0
4
0
1
Order By: Relevance
“…The interaction of thyroid hormone and contractile activity can be analyzed either by inhibiting spontaneous contractions (576) or by electrically stimulating the cells (575). The cell line H9C2, derived from rat embryonic heart tissue, is used as an alternative to primary cardiomyocyte cultures and various aspects of thyroidhormone action and metabolism have been studied in H9C2 cells (579)(580)(581). Although this cell line has retained a number of cardiomyocyte characteristics, it exhibits many of the key properties of skeletal muscle.…”
Section: And Recommendation 53mentioning
confidence: 99%
“…The interaction of thyroid hormone and contractile activity can be analyzed either by inhibiting spontaneous contractions (576) or by electrically stimulating the cells (575). The cell line H9C2, derived from rat embryonic heart tissue, is used as an alternative to primary cardiomyocyte cultures and various aspects of thyroidhormone action and metabolism have been studied in H9C2 cells (579)(580)(581). Although this cell line has retained a number of cardiomyocyte characteristics, it exhibits many of the key properties of skeletal muscle.…”
Section: And Recommendation 53mentioning
confidence: 99%
“…The implication of TR α 1 in cell differentiation is shown in embryonic myoblast cultures (H9c2), which is considered a suitable model to study cell differentiation. Maturation of H9c2 is TH dependent process [25, 26]. TR α 1 expression is increased in parallel with the intracellular T3 at the stage of cell differentiation and pharmacological inactivation of TR α 1 significantly delays cardiac myoblast maturation [27].…”
Section: Trα1 Receptor and Its Physiologic Actionsmentioning
confidence: 99%
“…fibroblasts, but not myocytes, synthesize and secrete glucuronidated iodothyronine conjugates in vitro, and it was subsequently shown that cells from the embryonic rat heart ventricle cell line H9c2(2-1) preferentially take up glucuronidated T4 and T3 over the native, unconjugated hormones (van der Heide et al, 2007;van der Heide et al, 2002). These findings support the r of conjugating and deconjugating enzymes in the m odulation of horm one bioactivities in an endocrine or paracrine fashion.…”
Section: Accepted Manuscriptmentioning
confidence: 83%